PROBLEMATIKA PENYUSUNAN BAHAN AJAR MENYIMAK KREATIF - Fauzi Fahmi (Jurnal Bahastra, 2021)
AbstractThe problems that occur in the preparation of listening teaching materials are still frequent. As for the problem of listening skills, first, the problem of listening competency test, second, the problem of technology stuttering and the availability of media experienced by the teacher, third, the problem of the conventional learning process, fourth, the problem of authentic assignment. This study uses a literature study method that relies on bibliographical sources from books and articles in scientific journals. 1) Planning for teaching materials that is carried out by the teacher in the form of selecting methods or strategies, media and learning steps that are implemented in the form of a learning implementation plan. 2) Implementation of the role of a teacher who excels in applying creative and innovative models, approaches, strategies, methods, techniques and tactics as well as media in the Indonesian language learning process, especially in listening skills. 3) The solution is given through the first, the listening competency test, second, the habituation of using technology and the availability of media, third, the creative and innovative learning process, fourth, the continuous authentic assignment.Keywords: Teaching Materials, Listening, Creative AbstrakProblematika yang terjadi dalam penyusan bahan ajar menyimak masih sering terjadi. Adapun problematikan keterampilan menyimak, pertama, permasalahan tes kompetensi menyimak, kedua, permasalahan gagap teknologi dan ketersediaan media yang dialami guru, ketiga, permasalahan proses pembelajaran yang konvensional, keempat, permasalahan penugasan otentik. Penelitian ini menggunakan metode studi kepustakaan yang mengandalkan sumber bibliografi dari buku dan artikel di jurnal ilmiah. 1) Perencanaan penyusuna bahan mengajar yang dilakukan oleh guru berupa, pemilihan metode atau strategi, media dan langkah-langkah pembelajaran yang diimplementasikan dalam bentuk rencana pelaksanaan pembelajaran. 2) Implementasi peranan seorang guru yang unggul dalam menerapkan model, pendekatan, strategi, metode, tehnik dan taktik serta media yang kreatif dan inovatif dalam proses pembelajaran bahasa Indonesia khsusunya dalam keterampilan menyimak. 3) Solusi yang diberikan melalui pertama, adanya tes kompetensi menyimak, kedua, pembiasaan menggunakan teknologi dan ketersediaan media, ketiga, Proses pembelajaran yang kretaif dan inovatif, keempat, Penugasan otentik secara kontinu.Kata Kunci: Bahan Ajar, Menyimak, Kreatif